AKTIVITAS HUMAS PT. PLN (Persero) WILAYAH RIAU DAN KEPULAUAN RIAU DALAM MENINGKATKAN CITRA POSITIF PERUSAHAAN - Ceisilia, Mega; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Public relation department has a big influence in company’s existence and positive image. Every institution, company, organization and government want positive image in society. To reach this, public relations department needs to do some activities like: publicity, media relations, and crisis management. PT. PLN (Persero) Wilayah Riau and Kepulauan Riau has some problems like scheduled extiguishing, low standard infrastructure and interconnection problem. These problems affect company’s image. The purpose of this research is to find out the activities of public relations department of PT. PLN (Persero) area of Riau and Kepulauan Riau in improving company’s positive image. The other purpose is to find out public relation media used by PT. PLN (Persero) area of Riau and Kepulauan Riau in improving company’s positive image.Writer used qualitative method. Analysis is shown descriptively. Data collecting technique are observation, interview, and documentation. To get validity of the data, writer used triangulation. Subject of this research is staff of Sub Bidang Humas Dan Hukum PT. PLN (Persero) area of Riau and Kepulauan Riau, customers, and journalists, decided by purposive technique sampling. Object of the research is public relations activity in improving company’s positive image.Result shows that activities of public relation of PT. PLN (Persero) are not maximal yet. It is shown by lack of acccurate information for customer, and slow response for problem facing by customers. Public relation media used to improve positive image contains mass media like newspaper and website, street banner, and bulletin Sawit e-news. Public relation media used are not effective yet, because the customers do not get fast and accurate information and also limited media used in spreading the information to society.Keyword: public relations activities, image, communication